Measurement of the time-dependent CP asymmetry in B → J/ψ K decays - Adametz, A; Bediaga, I; De Miranda, J; Diniz Batista, P; Ferreira Rodrigues, F; Magnin, J; Massafferri, A; Nasteva, I; dos Reis, A; Amato, S; Carvalho Akiba, K; De Paula, L; et al. (2010)
This Letter reports a measurement of the CP violation observables S and C in the decay channel B → J/ψ K performed with 1.0 fb of pp collisions at √s = 7 TeV collected by the LHCb experiment. The fit to the data yields S J/ψ K0 S = 0.73 ± 0.07 (stat) ± 0.04 (syst) and C = 0.03 ± 0.09 (stat) ± 0.01 (syst). Both values are consistent with the current world averages and within expectations from the Standard Model. © 2013 CERN.